Prevalence and Predictors of Intestinal Parasites among Food Handlers in Yebu Town, Southwest Ethiopia - Tefera, Tamirat; Mebrie, Getye (PloS one, 2014)
As a result of urbanization, eating and drinking from food service establishments is becoming a common practice in developing countries like Ethiopia, which increases the chances of food borne diseases. The health status and hygiene practices of food handlers are the major determinants of food contamination. In developing countries where there are poor regulatory systems for food hygiene, food handlers are often appointed without screening for possible infections associated with poor hygiene like intestinal parasites. This study aimed at determining the prevalence and predictors of intestinal parasites and assessing the hygiene practices among food handlers in Yebu Town, southwest Ethiopia. A cross-sectional study was conducted among a total of 118 food handlers in Yebu Town in January 2011. Fresh stool specimens were collected and processed using both direct wet mount and Formol ether concentration techniques. The overall prevalence of intestinal parasites among the study subjects was 44.1% (52/118). Ascaris lumbricoides and hookworm spp were the predominant parasites identified from the stool of study participants. Age above 35 years (AOR: 4.8, 95% CI: 1.1, 21.8), no regular practice of washing hands before a meal (AOR: 7.8, 95% CI: 2.8, 24.8), and untrimmed finger nail (AOR: 14.7, 95% CI: 2.8, 75.4) were independent predictors of intestinal parasitic infection among the food handlers. The present study showed high prevalence of intestinal parasites among the study subjects. The study also revealed poor personal hygiene like poor practice of hand washing and poor finger nail hygiene. Therefore, much has to be done to improve the personal hygiene of the food handlers. Pre-placement and periodic screening of food handlers for parasites and prompt treatment, and health education on regular trimming or cleaning of fingernails would be the way forward for prevention of food borne diseases.